An all thiol–ene microchip for solid phase extraction featuring an in situ polymerized monolith and integrated 3D replica-molded emitter for direct electrospray mass spectrometry. Issue 24 (8th June 2018) - Jönsson, Alexander; Lafleur, Josiane P.; Sticker, Drago; Kutter, Jörg P.
Abstract : Pre-concentration and clean-up are essential sample preparation steps in environmental, forensics and bio-analytical assays. Abstract : Pre-concentration and clean-up are essential sample preparation steps in environmental, forensics and bio-analytical assays. Here, we present work towards a fully integrated, replica molded all thiol–ene lab-on-a-chip solution for sample enrichment and mass spectrometry. A microfluidic chip based column, for solid phase extraction (SPE), was fabricated using thiol–ene as both bulk material and an in situ polymerized monolith. C11 -alkyl chains, in the form of undecanethiol, could be directly immobilized at the monolith surface, through the thiol–ene click reaction. Capacity of the produced SPE columns, for the test compound anthracene, was investigated by UV/Vis absorbance by connecting the chips to the detector of a commercial CE instrument with the help of a 3D-printed chip holder. The column capacity for anthracene was found to be ca. 14 μg m −2, which is consistent with the surface density of functional groups present at the monolith surface. The SPE column was further integrated with a unique on-chip electrospray ionization (ESI) emitter and hyphenated to an ion trap mass spectrometer. The emitter is directly replica molded in the process of chip fabrication, without any additional post-processing, and features a three-dimensional taper. The produced electrospray was investigated in the range of 250–370 m / z and found to be stable with a relative standard deviation of 8 ± 3%. Using the endogenous steroid progesterone, on-line extraction was also investigated on the SPE-ESI chip by direct infusion. Recoveries ranging from 40–50% indicated that further work is required to improve performance. However, the potential of an all-polymer, inexpensive device for sample clean-up featuring an integrated ESI emitter opens up an array of possibilities for applications in fields where single-use devices are mandatory, such as medical, biological, and pharmaceutical applications.